Pengaruh kompetensi dan kinerja sumber daya manusia dalam penerapan prinsip-prinsip Good Corporate Governance pada pegawai di Rumah Sakit Umum Daerah Provinsi Sulawesi Utara - Lydia Elvina Rindengan; Billy Johnson Kepel; Starry Homenta Rampengan; Aaltje Ellen Manampiring (DiscoverSys Inc., 2022)
Background: In supporting exist service, hospitals need competent employees and good performance of human resources in order to optimize organizational performance that implements the principles of good corporate governance. The purpose of this study was to analyze the effect of competence and performance of human resources in the application of the principles of good corporate governance at the Regional General Hospital of North Sulawesi Province.Method: This type of research is analytic observational with a cross sectional study approach. This research was carried out at the Regional General Hospital of North Sulawesi Province in February 2022. The research sample was taken from existing employees with a simple random sampling technique with a total of 182 samples of respondents. The inclusion criteria in this study were ASN and THL who worked at the Regional General Hospital of North Sulawesi Province. The data in this study were taken through the distribution of questionnaires and filled out by employees as respondents. Data analysis used univariate, bivariate and multivariate tests using SPSS version 25 for Windows. Result: Respondents of ASN employees were 104 people (57,1%) and THL were 78 people (42,9%). chi square test shows that there is an influence between competence and performance of human resources in the application of good corporate governance principles (p value<0,000). The logistic regression test shows that competence has a positive effect on the application of the principles of good corporate governance with an odd ratio of 29,234 and the performance of human resources has a positive effect on the application of the principles of good corporate governance with an odd ratio of 10,792. Competence and performance of human resources simultaneously affect the application of the principles of good corporate governance seen from the calculated chi square value is greater than the chi square table (88,895>5,991). Conclusion: Competence and performance of human resources partially have a positive effect on the application of good corporate governance principles to employees at the Regional General Hospital of North Sulawesi Province. Latar Belakang: Dalam menunjang pelayanan yang ada, rumah sakit membutuhkan pegawai yang kompeten dan juga kinerja sumber daya manusia yang baik dalam rangka optimalisasi kinerja organisasi yang menjalankan prinsip good corporate governance. Tujuan penelitian ini untuk menganalisis pengaruh kompetensi dan kinerja sumber daya manusia dalam penerapan prinsip-prinsip good corporate governance di Rumah Sakit Umum Daerah Provinsi Sulawesi Utara Metode: Jenis penelitian bersifat obsevasional analitik dengan pendekatan cross sectional study. Penelitian ini dilaksanakan di Rumah Sakit Umum Daerah Provinsi Sulawesi Utara pada bulan Februari 2022. Sampel penelitian diambil dari pegawai yang ada dengan teknik pengambilan sampel simple random sampling dengan jumlah responden sebanyak 182 sampel. Kriteria inklusi dalam penelitian ini adalah ASN dan THL yang bekerja di Rumah Sakit Umum Daerah Provinsi Sulawesi Utara. Data dalam penelitian ini diambil melalui pembagian kuesioner dan diisi oleh oleh pegawai sebagai responden. Analisis data menggunakan uji univariat, bivariat dan multivariat menggunakan SPSS versi 25 untuk WIndows. Hasil: Responden pegawai ASN 104 orang (57,1%) dan THL sebanyak 78 orang (42,9%). Uji chi square menunjukkan adanya pengaruh antara kopetensi dan kinerja sumber daya manusia dalam penerapan prinsip-prinsip good corporate governance (nilai p<0,000). Uji regresi logsitik menunjukkan kompetensi berpengaruh positif terhadap penerapan prinsip-prinsip good corporate governance dengan odd ratio 29,234 dan kinerja sumber daya manusia berpengaruh positif dalam penerapan prinsip-prinsip good corporate governance dengan odd ratio 10,792. Kompetensi dan kinerja sumber daya manusia berpengaruh secara simultan dalam penerapan prinsip good corporate governance dilihat dari nilai chi square hitung lebih besar dari chi square tabel (88,895>5,991). Kesimpulan: Kompetensi dan kinerja sumber daya manusia secara parsial berpengaruh positif dalam penerapan prinsip-prnsip good corporate governance pada pegawai di Rumah Sakit Umum Daerah Provinsi Sulawesi Utara.